Human Capital Spill-Overs Within the Workplace - Harminder Battu; Clive R. Belfield; Peter J. Sloane (Institute for the Study of Labor (IZA), 2001)
An individual?s human capital has a strong influence on earnings. Yet individual, worker-level estimations of earnings rarely include the characteristics of co-workers or detailed firm-level controls. In this paper, we use a unique matched worker?workplace dataset to estimate the effect on own earnings of co-workers? education. Our results, using the 1998 UK Workplace Employee Relations Survey, show significant effects. Own earnings premia fall slightly, but there is an independent, significantly positive effect from average workplace education. We also test for interactions between own and co-worker education levels. However, these interactions appear negative: education is valued less highly at workplaces where education levels are already high. This result runs counter to our theoretical prediction.
Keywords: J4; I2; 330; Educational economics; human capital; workplace performance; Bildungsertrag; Arbeitsplatz; Humankapital; Spillover-Effekt; Personalbestand; Theorie; Großbritannien